The effects of pediatric flat foot on the frontal alignment of proximal segment (Balneo and PRM Research Journal, 2022)
ABSTRACT: The purpose of this study was to determine the effects of flat foot on the frontal alignment of calcaneus and tibia in 23 children with flat feet, aged 7-9 (7.43±0.58 years old). To evaluate the foot, the Foot Posture Index-6 (FPI 6) was used, while the posture of the calcaneus and the tibia was analyzed using the Global Postural System 400. The statistical results indicate strong intensity links between flat foot and the frontal alignment of the calcaneus and the tibia, as follows: FPI 6 right foot score and calcaneus - right foot angle (r= 0.824; p < 0.001), tibia - right foot angle (r= 0.588; p < 0.001); FPI 6 left foot score and calcaneus - left foot angle (r= 0.824; p < 0.001), tibia - left foot angle (r= 0.853; p < 0.001). Our study demonstrates that pediatric flat foot has the capacity to significantly influence the values of the angle of the calcaneus and tibia in a frontal plane.